The Canine POMC Gene, Obesity in Labrador Retrievers and Susceptibility to Diabetes Mellitus. (8th February 2017) - Davison, L.J.; Holder, A.; Catchpole, B.; O'Callaghan, C.A.
Abstract : Background: Diabetes mellitus (DM) in dogs is a common endocrinopathy with a complex genetic architecture. Disease susceptibility in several breeds is associated with polymorphisms in immune response genes, but in the Labrador retriever breed, no genetic associations with DM have been identified. A deletion in the pro‐opiomelanocortin ( POMC) gene in Labrador retrievers is associated with increased appetite and risk of obesity. Hypothesis/Objectives: To characterize the POMC deletion in Labrador retrievers, to develop a simple genetic test for this mutation, and to test the hypothesis that the POMC gene deletion is associated with an increased risk of DM in this breed. Animals: Sixty‐one non‐diabetic Labrador retrievers aged >6 years and 57 Labrador retrievers with DM. Methods: Case–control genotyping study to compare the frequency of the POMC deletion in dogs with and without DM. After polymerase chain reaction (PCR) and sequencing to characterize the mutation, a PCR‐based test was developed and validated using 2 different restriction fragment length polymorphism assays. Results: A 14‐base‐pair deletion was confirmed and localized to exon 3 of the canine POMC gene. A PCR‐based test for the deletion was successfully developed. There was no association between the presence of the POMC deletion mutation and DM in this population of Labrador retriever dogs ( P  = .31). Conclusions and Clinical Importance: This study adds to the existing scientific literature indicating that there is little evidence for a direct link between obesity and DM in dogs.